Development and Initial Validation of the Volition in Exercise Questionnaire (VEQ). Issue 2 (3rd April 2017) - Elsborg, P.; Wikman, J. M.; Nielsen, G.; Tolver, A.; Elbe, A.-M.
ABSTRACT: The present study describes the development and validation of an instrument to measure volition in the exercise context. Volition describes an individual's self-regulatory mental processes that are responsible for taking and maintaining a desirable action (e.g., exercising regularly). The scale structure was developed in an exploratory factor analysis which resulted in a reliable structure of the following six factors: Volitional Inhibition—Reasons, Volitional Inhibition—Postponing Training, Volitional Facilitation—Self-Confidence, Volitional Inhibition—Unrelated Thoughts, Volitional Inhibition—Approval From Others, and Volitional Facilitation—Coping with Failure . A sound theoretical explanation for these six factors is based on the Personal System Interaction Theory. This six-factor structure was also confirmed in a new sample in a confirmatory factor analysis, delivering an 18-item questionnaire with strong model fit and good internal consistency. In addition, the Volition in Exercise Questionnaire showed convergent validity because it was able to predict exercise participation. It showed incremental validity by explaining additional variance to the Sport Motivation Scale's well-established predictors of exercise participation.